Chromosomální aberace v etiologii potratů po lécbĕ sterility metodou IVF a ET - Mardesic, T; Nejezchlebová, L; Subrt, I; Müller, P; Voboril, J; Zetová, L; Grocholová, B; Miková, M (Ceska gynekologie, 1996)
Chromosomal aberrations are a frequent cause of miscarriages during the first trimester of gestation. The most frequent finding in the authors group was trisomy 16 (in five patients). After extracorporeal fertilization (IVF) the percentage of abnormal karyotypes does not increase, the main risk factor being the women's age.
Keywords: první trimestr těhotenství; Trisomy; samovolný potrat; lidské chromozomy, pár 16; těhotenství; rizikové těhotenství; Adult; trizomie; Pregnancy Trimester, First; věk matky; Fertilization in Vitro; Pregnancy, High-Risk; ženské pohlaví; Humans; přenos embrya; Pregnancy; Abortion, Spontaneous; Chromosome Aberrations; chromozomální aberace; rizikové faktory; fertilizace in vitro; dospělí; Embryo Transfer; Female; Risk Factors; Chromosomes, Human, Pair 16; lidé; Maternal Age